Exploring perceived restoration, landscape perception, and place attachment in historical districts: insights from diverse visitors - Li, Jiaying; Luo, Junjie; Deng, Tangmin; Tian, Jingwen; Wang, Hongcheng (Frontiers in Psychology, 2023)
Improving the quality of the built environment to enhance people’s mental health is gaining traction across various fields, precipitating valuable actions on the wave of “Healthy China 2030” initiative. While ample studies have confirmed the benefits of interaction with natural or green spaces, the investigation into the restorative potential in urban built settings remains notably underexplored. In this study, we focused on historical districts, conducting a questionnaire survey to evaluate the restorative experiences of individuals visiting these sites. We used structural equation model (PLS-SEM) to analyze a conceptual model that encompasses landscape perception, place attachment, and perceived restoration, with a specific focus on detecting the mediating role of place attachment and the moderating influence of visitor groups. The results showed that landscape perception significantly influenced the perceived restoration, which contained the indirect effect pathway through place dependence and place identity, as well as the potent direct impact of landscape perception. Moreover, employing a multi-group analysis (MGA), we discerned that different visitor groups partially moderate the relationship between landscape perception, place attachment, and perceived restoration. This study validates the restorative features in historic districts and highlights the importance of cognitive-emotional bond in promoting psychological restoration.